Green space and physical activity: An observational study using Health Survey for England data - Mytton, O; Mytton, O; Townsend, N; Townsend, N; Rutter, H; Rutter, H; Foster, C; Foster, C (2012)
Past studies have suggested that a link between health outcomes and green space is due to increased levels of physical activity of individuals living in areas with more green space. We found a positive association between green space and physical activity levels. The odds of achieving the recommended amount of physical activity was 1.27 (95% CI: 1.13-1.44) for people living in the greenest quintile in England compared to those living in the least green quintile, after controlling for individual and environmental factors. However, no association was found between green space and types of physical activity normally associated with green space. An association was found with other types of physical activity (gardening and do-it-yourself, and occupational physical activity). These findings suggest that although there is a positive association between physical activity and green space it may not be explained by individuals using green space for recreation. © 2012 Elsevier Ltd.